2015
DOI: 10.1016/j.febslet.2015.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan silencing by engineered CXCL12 variants

Abstract: a b s t r a c tWe have engineered GPCR (G protein-coupled receptor) knock-out and high GAG-binding affinity into CXCL12a to inhibit CXCL12a-induced cell migration. Compared to wtCXCL12, the mutant CXCL12a (D8 L29K V39K) exhibited a 5.6-fold and a 2.2-fold affinity increase for heparin and heparan sulfate, respectively. From NaCl-based heparin displacement chromatography we concluded that more amino acid replacements would lead to altered GAG (glycosaminoglycan) ligand specificity. GAG silencing by this mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Recently, inhibition of chemokine–GAG interaction has been explored as a complementary alternative for chemokine receptor antagonists. Both modified chemokines with enhanced GAG interaction and reduced activity on GPCRs, and aptamers that interfere with chemokine–GAG binding have entered clinical development (40, 41). The COOH-terminal CXCL9 domain CXCL9(74-103) potently bound GAGs, competed for GAG binding with several chemokines and was able to inhibit CXCL8- and MSU crystal-induced leukocyte migration to joints (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, inhibition of chemokine–GAG interaction has been explored as a complementary alternative for chemokine receptor antagonists. Both modified chemokines with enhanced GAG interaction and reduced activity on GPCRs, and aptamers that interfere with chemokine–GAG binding have entered clinical development (40, 41). The COOH-terminal CXCL9 domain CXCL9(74-103) potently bound GAGs, competed for GAG binding with several chemokines and was able to inhibit CXCL8- and MSU crystal-induced leukocyte migration to joints (42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PA401, a CXCL8-based decoy protein, exerts strong anti-inflammatory activity in vivo (3538). Also CCL2- and CXCL12-based decoy proteins with high GAG-binding affinity and reduced activity on GPCRs have been developed (39, 40). Interference with GAG interactions also forms the basis for the inhibition of lymphocyte migration with the spiegelmer NOX-A12 (41).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of this mutant was assessed in an in vivo murine breast cancer seeding model. Treatment with the CXCL12α mutant inhibited migration of cancer cells, resulting in a decreased number of liver metastases (281).…”
Section: Dominant-negative Chemokine Mutantsmentioning
confidence: 99%
“…A variant of CXCL8 which has no ability to bind GPCRs but with increased GAG binding affinity inhibits trans-endothelial migration of neutrophils by displacing CXCL8 from the surface of endothelial cells [ 114 ]. A similar study by our group showed that a non-GPCR binding, increased-GAG binding CXCL12 variant showed a reduction in cell migration [ 115 ]. A CCL2 mutant with increased GAG binding was shown to displace multiple chemokines which could overcome the issues of redundancy [ 116 ], however high concentrations of chemokine may be required to occupy binding sites on all GAGs [ 43 , 117 ].…”
Section: Gags Nitration and Cxcl8 Functionmentioning
confidence: 98%